Teachers’ Professional Competence in Integrating Technology: A Case Study at English Teacher Forum in Majalengka - Agus Rofi’i; Eka Nurhidayat; Hastri Firharmawan (IJLECR (International Journal of Language Education and Cultural Review), 2023)
This article presents a case study at the English Teacher Forum in Majalengka, focusing on improving teachers' professional competence in integrating technology into their teaching practices. The study addresses teachers’ challenges in effectively incorporating technology and explores strategies to enhance their skills and abilities. The qualitative research methodology uses a case study approach using structured interview techniques and document analysis. The findings reveal that many teachers in the forum lack the confidence and skills to integrate technology effectively, hindering digital tools' educational potential. However, significant improvements were seen in the professional competence of English teachers, such as mastering teaching materials, being able to manage classes, being able to use media and learning resources, mastering educational foundations, being able to manage learning interactions, and being able to assess learning achievement for the benefit of learning through development programs professionalism, peer coaching, access to resources, and ongoing support. Students also demonstrated increased motivation and improved learning outcomes. The study highlights the importance of ongoing support and training for teachers and the need for technological infrastructure investment. The research findings and recommendations aim to guide educators and policymakers in promoting technology-integrated learning environments in Majalengka and similar contexts, ultimately enhancing student learning experiences and outcomes.